Les oeuvres complètes de Voltaire. 73, Writings of 1771. - Voltaire, 1694-1778.; Smith, Martin (Oxford : Voltaire Foundation, 2004)
The writings gathered together in volume 73 of the Complete works were substantially written in 1771, when Voltaire was seventy-six years old. Despite periods of illness and difficulties with his failing eyesight, Voltaire maintained a literary output of astonishing energy and variety. His commitment to la philosophie, his political convictions, and his emerging passion for justice, led him to participate in crucial public debates. In the 'age of reform' which was beginning, Voltaire eagerly took up the challenge of influencing events with his writings.
JSTOR
Keywords: French prose literature -- 18th century; Prose française -- 18e siècle.